2020
DOI: 10.1016/j.isci.2020.101760
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Damage to Prepubertal Pax7+ Skeletal Muscle Stem Cells Drives Lifelong Deficits in Myofiber Size and Nuclear Number

Abstract: Summary During prepubertal development, muscle stem cells (satellite cells, SCs) actively contribute to myofiber growth. Because some SCs are active during this time, they may be particularly susceptible to damage. Using a Small Animal Radiation Research Platform (SARRP), we investigated the effects of local fractionated radiation treatment on prepubertal SCs. Immediately after this regimen, there was a reduction in SC number. Although surviving SCs had deficiencies in function, some myogenic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 74 publications
6
59
0
Order By: Relevance
“…To evaluate transcriptomic changes in skeletal muscle across our experimental groups, we performed RNA-sequencing analysis. We previously published the transcriptomic effects of paediatric radiation alone (GSE160064), 5 S1).…”
Section: Up-regulated Inflammatory and Fibrotic Gene Expression After Paediatric Radiotherapymentioning
confidence: 99%
“…To evaluate transcriptomic changes in skeletal muscle across our experimental groups, we performed RNA-sequencing analysis. We previously published the transcriptomic effects of paediatric radiation alone (GSE160064), 5 S1).…”
Section: Up-regulated Inflammatory and Fibrotic Gene Expression After Paediatric Radiotherapymentioning
confidence: 99%
“…Second, mice have a rapidly developing musculoskeletal system, and mice are relatively inexpensive, which makes them an economic choice for large sample size studies 27 . Various groups have used mouse models of muscle stem cell depletion to examine the contribution to sarcopenia‐related phenotypes 28–31 . Among them, Liu et al 31 .…”
Section: The Importance Of Mouse Models Of Sarcopeniamentioning
confidence: 99%
“…103,104 An emerging body of pre-clinical evidence indicates that irradiation-induced satellite cell depletion impairs the response to hypertrophic stimuli. 104,105 Further, it appears as though the impact of radiation on skeletal muscle morphology might be dose dependent and influenced by fibre type. In 2014, Hardee et al demonstrated muscle protein and RNA content were reduced with a single 16 Gy dose of radiation, but not with four fractionated doses of 4 Gy.…”
Section: Radiotherapymentioning
confidence: 99%
“…Long-term follow ups of individuals who have received treatment for child/young adult cancer reveal persistent impairments in muscular function and tissue decline. 105 However, much less is known of the persistent and/or late effects of cancer and its therapies on signalling pathways once treatment has finished. In adult cancers, untangling the impact of natural ageing, diet, and inactivity on these pathways, vs. the sustained, or late effects of treatments is difficult.…”
Section: How Long Aberrations In Muscle Signalling and Pathology Persist After Treatmentmentioning
confidence: 99%